SISTEMATIZAÇÃO DA ASSISTÊNCIA DE ENFERMAGEM A UM PACIENTE COM GLOMERULONEFRITE DIFUSA AGUDA-GNDA - Simplício Teixeira, Suênia Évelyn; Maria Araújo Farias, Layanne; Albuquerque Machado, Átilla Maria; Mendes Barbosa, Carlos Henrique; Luana Trajano Aguiar, Nara; Montenegro Santiago, Luciana Maria (SANARE - Revista de Políticas Públicas, 2015)
-